The Effect of Intramuscular Onusetron Treatment on Prognosis in Patients Diagnosed with Acute Gastroenteritis - İlknur Bodur; Betül Öztürk; Aytaç Göktuğ; Raziye Merve Yaradılmış; Muhammed Mustafa Güneylioğlu; Ali Güngör; Can Demir Karacan; Nilden Tuygun (Journal of Pediatric Emergency and Intensive Care Medicine, 2023)

(untitled)
Introduction:Vomiting is an important symptom that limits oral intake and may result in hospitalizations and prolonged hospital stays for intravenous fluid therapy. In our study, we aimed to compare the rates of hospital revisit and hospitalization due to vomiting within seven days of admission in children with acute gastroenteritis in two groups who received and did not receive intramuscular ondansetron.Methods:Files of patients aged 6 months-15 years (without dehydration) diagnosed with acute gastroenteritis (ICD A09) in our pediatric emergency clinic between December 2015-February 2016 (non-ondansetron period) and December 2019-February 2020 (intramuscular ondansetron period) were analyzed retrospectively. The patients included in the study were evaluated in two groups, the first group receiving a single dose of intramuscular ondansetron and the second group not receiving ondansetron treatment. Our primary aim was to determine the rates of readmission and hospitalization in the first 7 days of both groupsResults:It was determined that 21% of the patients who received ondansetron and 28% of the group who did not receive ondansetron were admitted to the emergency department due to vomiting in the first 7 days. In comparison of both groups, 5% of group I patients and 13% of group II patients needed intravenous fluids (odds ratio =0.3; 95% confidence interval =0.19-0.59) at repeated admission and required hospitalization in the emergency department.Conclusion:Intramuscular ondansetron treatment reduces the rate of hospital readmission, hospitalization and intravenous fluid requirement during re-admission in children with acute gastroenteritis with vomiting.